BODY MASS INDEX, BODY DISSATISFACTION, AND SOCIAL ENVIRONMENT CORRELATED TO UNHEALTHY DIETARY BEHAVIORS IN ADOLESCENT GIRLS - Diva Amalia; Tri Rejeki Andayani; Sapja Anantanyu (Universitas Airlangga, 2023)
The physical changes in adolescent girls raise concerns about body weight and shape, thus encouraging adolescents to go on a weight-control diet is necessary. This study aimed to analyze the relationship between body mass index, body dissatisfaction, and social environment on unhealthy diet behaviors of adolescent girls. This study used a cross-sectional design with 80 adolescent girls aged 16-18 years recruited as the study participants by purposive sampling. Data were obtained from height and weight measurements, the Body Shape Questionnaire (BSQ-34), the social environment questionnaire, and the diet behavior questionnaire. Analysis of the relationship between variables using Somers'd test. The results of this study indicated that most of the respondents were 16 years old (53.8%), had good nutritional status (58.8%), and had daily pocket money of 15,000-20,000 IDR (51.3%). There was a correlation between body mass index (p < 0.001, d = 0.545), body dissatisfaction (p < 0.001, d = 0.624), and social environment (p < 0.001, d = 0.697) on unhealthy diet behavior in adolescent girls. Wrong perceptions of body weight status will increase dissatisfaction with the body and quickly get pressure from the social environment, thus encouraging the desire to go on a diet to control weight which tends to be unhealthy. Therefore, preventing unhealthy diet behavior in adolescent girls can be done by providing nutritional education about calculating body mass index values and efforts to control healthy weight.